1969
DOI: 10.2307/3896341
|View full text |Cite
|
Sign up to set email alerts
|

Soil Depth-Vegetation Relationships on a Shallow Limy Range Site in Western Kansas

Abstract: Highlight Soil depth heterogeneity within the shallow limy range site in western Kansas results in differences in range composition and production. Deep soils produce more forage than shallow (< 4") soils. Such variations in production within an apparently uniform range site should be considered when evaluating range condition and establishing stocking rates. Study Area and Procedure Two sampling areas were used in this project. Twohundred samples were taken from a 320-acre grassland

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1970
1970
1996
1996

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Increased soil depth and consequent increased soil volume, which provided greater moisture storage, exerted the major influence on the vegetation pattern and production. Hulett et al (1969) found similar relationships in limestone grasslands of Kansas. Three stands were qualitatively selected on the basis of apparent high, medium, and low production (Fig.…”
Section: Woody Species Covered Approximatelymentioning
confidence: 57%
“…Increased soil depth and consequent increased soil volume, which provided greater moisture storage, exerted the major influence on the vegetation pattern and production. Hulett et al (1969) found similar relationships in limestone grasslands of Kansas. Three stands were qualitatively selected on the basis of apparent high, medium, and low production (Fig.…”
Section: Woody Species Covered Approximatelymentioning
confidence: 57%
“…Shallow soils have been shown to limit the growth of rangeland vegetation (Hulett et al, 1969), cotton (Lowry et al, 1970), grapes (Morris and Cawthon, 1981), and maize (Frye et al, 1983). Quantitative data on the influence of root-restricting layers on cereal crops are needed to assess the productivity of soils containing petroferric horizons, and the effect of erosion on soil productivity: however, such data are lacking.…”
Section: Introductionmentioning
confidence: 99%